A turn on and a turn off: BLT1 and BLT2 mechanisms in the lung. (August 2014) - Watanabe, Masaki; Machida, Kentaro; Inoue, Hiromasa
<x xml:space="preserve">Abstract</x> Leukotriene B4 (LTB4), a potent lipid mediator of inflammation derived from arachidonic acid through the action of 5-lipoxygenase, has been implicated in the pathophysiology of several inflammatory diseases, including asthma and chronic obstructive pulmonary disease. A high-affinity LTB4 receptor BLT1 has been shown to exert proinflammatory roles. A cyclooxygenase metabolite, 12(S)-hydroxyheptadeca-5Z, 8E, 10E-trienoic acid (12-HHT), is an endogenous ligand for BLT2, a low-affinity LTB4 receptor. The recent study indicated that BLT2 has a protective role in allergic airway inflammation, suggesting different functions between BLT1 and BLT2 in the pathogenesis of asthma. Selective BLT1 antagonists may have a potential therapeutic application in patients with asthma, and BLT2 may represent a novel therapeutic target for lung diseases.